Environmental Perspective of Russia's Accession to the World Trade Organization - World Bank (Washington, DC, 2014)
Russia's exports, imports, and ability to attract foreign direct investment (FDI) continue to grow. In December 2011, after eighteen years of negotiations, the World Trade Organization (WTO) invited Russia to join WTO on the basis of the negotiated protocol of Russian accession. Russia ratified the agreement in July 2012. As part of its accession to the WTO, Russia agreed to a series of important commitments to further open its trade and foreign investment regimes. Russia will apply international standards on sanitary measures and technical barriers to trade. Policies which promote energy efficiency, technology innovation, clean production in supply chains, and addressing climate change are receiving increasing attention in Russian society, and nowadays, shape the economic modernization agenda of the Russian political leadership. This report is designed to provide senior Russian policy makers with recommendations on certain areas where national environmental protection policies can be complemented by the benefits of trade liberalization. Industrial leaders may also benefit from many of the report's conclusions and recommendation. The report has several objectives. The first is to draw attention to the local impacts of air pollution impacting human health which has been previously estimated to be between 12 and 17 percent of all-cause mortality in Russia and costing the economy upwards of 14 billion dollars annually. Correcting for this "external cost" to society is not trivial and has serious implications for sector reform. The second objective is about reducing global warming, and in particular carbon dioxide (CO2). Russia's commitments to reducing greenhouse gas emissions have adjustment costs to the economy and the modeling undertaken in this report provides some relative magnitude. The third objective is related to the technological modernization that needs to take place in order to realize cost reductions (efficiency improvements) and what the associated environmental benefits will be. Finally, the report also demonstrates how the Government can reduce the marginal cost of funds from Russia's tax system. What this means is that money is currently being spent (tax Rubles) in an inefficient manner - either through large subsidies or funding inefficient production and consumption. The model investigates the impacts of trade liberalization through three impacts: the change in production output (the scale effect), sector mix (the composition effect), and productivity (the technique effect). The model highlights several areas where benefits can lead to better protection of the environment, and where liberalization measures can significantly enhance the effectiveness of national policies to address key environmental challenges. This report discusses Russia's accession to WTO from this perspective.